Delaware Opioid Metric Intelligence Project (DOMIP), 2013-2020 - Anderson, Tammy L. ([Verlag nicht ermittelbar], 2022)
The Delaware Opioid Metric Intelligence Project (DOMIP) provides community surveillance capabilities in Delaware to help reduce its prescription and illicit drug problems. DOMIP achieves this by integrating data on overdose deaths, crime, population characteristics and community resources into a user-friendly web application called the DOMIP Mapping app.